Dinamika Opini Publik di Media Sosial Tiktok : Analisis Sentimen Netizen terhadap Wisuda Ala Sarjana SMK Citra Bangsa Mandiri Purwokerto pada @republikajogja - Fahrudin, Atef; Wulandari, Ajeng Ayu (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
This study aims to examine the dynamics of public opinion on TikTok regarding the university-style graduation ceremony organized by SMK Citra Bangsa Mandiri Purwokerto. Employing a mixed-methods approach that integrates sentiment and framing analysis, a total of 285 user comments were analyzed through quantitative and qualitative techniques. Sentiment analysis revealed a predominance of negative comments at 89.1 percent, followed by neutral comments at 10.9 percent, with no positive sentiment identified. This distribution reflects an extreme polarization of opinion and a symbolic legitimacy crisis. The dominant frame focused on the inappropriate use of academic terminology, while the moral frame, though infrequent, achieved the highest level of engagement. The study underscores the role of emotional narratives in shaping public perception and highlights how social media algorithms amplify controversial content. These findings contribute to the development of digital media studies in Indonesia and provide practical implications for educational institutions and policymakers in addressing culturally sensitive public issues.